POLA PENGASUHAN ORANGTUA MILENIAL - Rahmawati, Novi Rosita; Septiana, Nila Z.; Karina, Karina; Masitoh, Fitriatul (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
This study is intended to describe millennial parenting in early childhood education. The method used in this study was a descriptive survey.  86 participants involved in this study, aged between 20 to 23 years old, are from around Indonesia. The results indicate that millenial parents; (1) buy books, join seminar, workshop, and a certain community to educate early childhood; (2) tend to provide facilitating bases for the needs of child’s growth; (3) are interested in enrolling their children in non-formal activities in order to explore the children talent; (4) take part totally in children care; and (5) seen from financial view, millennial parents are able to accomplish non-formal activities as a support for children care. This proves that the era of the industrial revolution 4.0 provides many differences in various aspects of life, mostly in the mindset, mindset and pattern of relationships related to parenting applied in the family. The development of the internet is used to study and this does not rule out the possibility of sharing knowledge with communities engaged in early childhood education.